HUBUNGAN PENINGKATAN BERAT BADAN IBU HAMIL DENGAN BERAT BADAN BAYI BARU LAHIR - Retno Dewi Prisusanti; Septiana Juwita (Oksitosin : Jurnal Ilmiah Kebidanan, 2018)
Pregnancy is the most important time mother prepares to welcome her babies so she can delivery her babies with healthy, perfect and the body weight of babies is sufficient. Pregnant need to achieve sufficient weight gain. The aim of study was find out of correlation between improvement of body weight pregnant with newborn baby of body weight. Analytical correlation design study. Sampling used to accidental sampling as many as 35 respondents were taken from inpartu mothers in RSIA Husada Bunda Malang. Collecting data with body weight of pregnant by looking at status of mother, weighing it pregnant who will delivery, questionnaires, weighing newborn babies. Analysis used to Pearson Product Moment correlation. Results of study were respondents who had a weight gain of <10 kg as many as 7 people (20%) and babies born had a weight between 2.75-3.5 kg, respondents who weighed between 10-12 kg were 17 people ( 48.6%) and babies born weigh between 2.2-3.6 kg, respondents who weigh> 12 kg are 11 people (31.4%) and babies born weigh between 2.15 -4.2 kg. The results of analysis obtained r count 0.197 <r table 0.334. The body weight pregnant was not correlated with newborn of body weight. Keywords: Body Weight, Pregnant, Newborn Baby. ABSTRAK Kehamilan merupakan waktu terpenting ibu mempersiapkan diri menyambut kelahiran bayinya sehingga ibu dapat melahirkan bayi sehat, sempurna dan berat badan bayi baru lahir cukup. Ibu hamil perlu mencapai kenaikan berat badan yang cukup. Tujuan penelitian untuk mengetahui hubungan peningkatan berat badan ibu hamil dengan berat badan bayi baru lahir. Desain penelitian analitik korelasi. Pengambilan sampel menggunakan accidental sampling sebanyak 35 responden diambil dari ibu inpartu di RSIA Husada Bunda Malang. Pengumpulan data dengan penimbangan berat badan ibu sebelum hamil dengan melihat status ibu, penimbangan berat badan ibu hamil yang akan melahirkan, angket, penimbangan berat badan bayi baru lahir. Analisa data menggunakan korelasi Pearson Product Moment. Hasil penelitian yaitu responden yang memiliki peningkatan berat badan < 10 kg sebanyak 7 orang (20%) dan bayi yang dilahirkan memiliki berat badan antara 2,75-3,5 kg, responden yang memiliki berat badan antara 10-12 kg sebanyak 17 orang (48,6%) dan bayi yang dilahirkan memiliki berat badan antara 2,2-3,6 kg, responden yang memiliki berat badan > 12 kg sebanyak 11 orang (31,4%) dan bayi yang dilahirkan memiliki berat badan antara 2,15-4,2 kg. Hasil analisa didapatkan r hitung 0,197 < r tabel 0,334. Peningkatan berat badan ibu hamil tidak ada hubungan dengan berat badan bayi baru lahir. Kata Kunci: Berat Badan, Ibu Hamil, Bayi Baru Lahir.